(untitled) (Talenta Conference Series: Science and Technology (ST), 2019)
The objective of the research is to increase the thermal stability of -amylase from Bacillus subtilis ITBCCB148 by immobilization using zeolite. For that reason, firstly we need to produce, isolate, and purify the enzyme. The purification of the enzyme was conducted by the following steps: fractionation with ammonium sulphate, dialysis, and CM-cellulose cation exchange column chromatography. The purified enzyme was immobilized using zeolite. The success in immobilization of the enzyme was evaluated by comparing the thermal stability of the enzyme before and after immobilization. Activity of α-amylase was determined by the Mandels and Fuwa method. The protein content was determined based on the method by Lowry. The results showed that the specific activity of purified enzyme was 2473.7 U / mg, increased 19 times compared to crude extract of enzyme having specific activity of 1285.9 U / mg. The purified enzyme has the optimum temperature at 65ºC, while the immobilized enzyme has the optimum temperature at 75ºC. The thermal stability test of the purified enzyme at 65ºC for 100 minutes showed the purified enzyme having residual activity of 20%; t 1 / 2 = 30 min, k i = 0.023 min -1 and ΔGi = 103.65 kJ mol -1 . The thermal stability test of the immobilized enzyme at 65ºC for 100 minutes showed that the immobilized enzyme had residual activity of 40%; t 1/ 2 = 49 min, k i = 0.014 min -1 and ΔGi = 105.03 kJ mol -1 . Immobilization using zeolite has succeeded in increasing the thermal stability of enzyme by 1.64 times compared to the purified enzyme, which is indicated by the decreasing of k i value, the increase of half-life and denaturation energy change (ΔGi).